Rancang Bangun Sistem Informasi Pengarsipan Dokumen Di Kantor Camat Segedong Berbasis Web - Santi, Santi; Murni, Sri; Handayani, Kartika; Erni, Erni; Rahayuningsih, Panny Agustia; Hasan, Fuad Nur (LPPM Universitas Bina Sarana Informatika, 2025)
In accordance with Pontianak District Regulation No. 7 of 2005, which formally established Segedong District, it was created by dividing Siantan District, which is now Jongkat District. Document archiving, including the recording of arriving and outgoing letters, is an integral part of the work of the Segedong Camat Office, a government agency in Segedong that provides services. The Segedong Sub-District Office has an issue with document archiving; specifically, they still use an agenda book to manually record incoming and outgoing letters. There is a risk of data corruption or loss while using the agenda book to record letters. The Segedong Sub-District Office is in need of an information system for web-based archiving. The research methodology involves conducting interviews and direct observations of the Segedong District Office's document filing system. In response to the challenges encountered by the Segedong District Office's staff in the process of document archiving, the author proposes the development of a web-based document archiving information system. Development of websites in PHP with the help of Xampp and MySQL. data pertaining to outgoing mail, index, reports on arriving mail, and reports on outgoing mail